EFL Students’ Experiences of Video Project Making in Teaching English for Young Learner Class - Nur Hasanah Safei; Yusdiawati, Nur Rahma; Syukri, Suhartini (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This study aims to investigate EFL students’ experiences of video project making in Teaching English for Young Learners class. Thematic analysis methods were used to analysed qualitatively the written reflections of five EFL students from English Education department. This study found that some of EFL students impressed positive toward making video storytelling. It also found that they did some preparation such as looking for several fairy tales types from various sources, selecting one story, composing dialogues, and dividing roles. Systematic stages, proceeding with benefits and challenges were found as well in their phase of making video storytelling. The implication of this study pedagogically is better for the educators and students in minimizing errors and deficiencies that occur in online collaborative project. It is also beneficial for EFL students to have digital literacy and digital skills in the near future.